Morph-physiology and development of soybean cultivars under irrigation shift - Lisboa, Lucas Aparecido Manzani; Menezes, João Victor de Souza (Revista de Ciencias Agrícolas, 2023)
During certain periods of the year, some Brazilian regions impose water restrictions, initiating the growth cycle of the soybean crop. Thus, this work was conducted aiming to evaluate the morphophysiology and development of soybean cultivars under irrigation intervals. The experiment was conduct in January 2021, in a rural property, located in the municipality of Lavínia, state of São Paulo, Brazil. The design was completely randomized, in a 2×5 factorial scheme, with two soybean cultivars, M7110IPro (Monsoy®) and Desafio RR8473RSF (Brasmax®), interacting with the irrigation intervals (i.e., 24 h (Control); 48 h; 72 h, 96 h and 120 h) totalizing 10 treatments. We used four repetitions per treatment, which totalizes 40 plots or pots. Our results revealed that intervals longer than 48 h already negatively influence in morphophysiology of the soybean crop. Intervals of 96 h caused greater negative interferences on plant height (PH); number of leaflets (NL); number of pods (NP); dry mass of aerial part (DMAP) and root (DMR) in the soybean crop when grown in pots. Water stress did not influence the stomatal density of soybean grown in pots. Water stress harms soybean physiological parameters. No soybean cultivar showed tolerance to water stress.